Banking carbon: a review of organic carbon storage and physical factors influencing retention in floodplains and riparian ecosystems. Issue 1 (16th December 2015) - Sutfin, Nicholas A.; Wohl, Ellen E.; Dwire, Kathleen A.
Abstract: Rivers are dynamic components of the terrestrial carbon cycle and provide important functions in ecosystem processes. Although rivers act as conveyers of carbon to the oceans, rivers also retain carbon within riparian ecosystems along floodplains, with potential for long‐term (> 10 2 years) storage. Research in ecosystem processing emphasizes the importance of organic carbon (OC) in river systems, and estimates of OC fluxes in terrestrial freshwater systems indicate that a significant portion of terrestrial carbon is stored within river networks. Studies have examined soil OC on floodplains, but research that examines the potential mechanistic controls on OC storage in riparian ecosystems and floodplains is more limited. We emphasize three primary OC reservoirs within fluvial systems: (1) standing riparian biomass; (2) dead biomass as large wood (LW) in the stream and on the floodplain; (3) OC on and beneath the floodplain surface, including litter, humus, and soil organic carbon (SOC). This review focuses on studies that have framed research questions and results in the context of OC retention, accumulation and storage within the three primary pools along riparian ecosystems. In this paper, we (i) discuss the various reservoirs for OC storage in riparian ecosystems, (ii) discuss physical conditions that facilitate carbon retention and storage in riparian ecosystems, (iii) provide a synthesis of published OC storage in riparian ecosystems, (iv) present a conceptual model of the conditions that favor OC storage in riparian ecosystems, (v) briefly discuss human impacts on OC storage in riparian ecosystems, and (vi) highlight current knowledge gaps. Copyright © 2015 John Wiley & Sons, Ltd.